The Implication of Students’ Psychological Aspects on Learning Difficulties Experienced by Students in Learning in School - Nupiah, Alhusna; McCulley, Walter; He, Tao (Al-Hijr: Journal of Adulearn World, 2022)
The learning process will involve the roles of teachers and students. There will be a process of mutual influence to achieve the desired common goal, namely a change with positive results from the entire series of teaching and learning activities carried out. However, in reality, teachers often face students with various learning difficulties that they experience. This is based on multiple factors, one of which is the problem of different student characteristics, both physiological and psychological. The scope of the psychological aspects of students includes the level of student intelligence/intelligence, student attitudes, student talents, student interests, and student motivation which can affect the achievement of student learning outcomes because the learning outcomes obtained by students will never be separated as a result of the high. Low psychological aspects possess students, so later, it will affect the learning difficulties experienced by students due to the standard psychological elements they have. Students' learning difficulties must be known to find appropriate problem-solving solutions. To overcome these student learning difficulties, it is necessary to analyze all psychological aspects of students to see the extent to which the interrelationships of each of these psychological aspects can cause learning difficulties in students.